Feasibility of a Qualitative Study Exploring the Experience of Deaf Individuals from Malaysia Studying Abroad: A Preliminary Study - NurFarhana A. Aftar (Asian Social Work Journal, 2021)
This is a feasibility qualitative study involving a triangulation data collection method. The aim of the study is to develop a qualitative research to explore the lived experience of deaf individuals in attempt to view and understand their experience from their perspectives. This preliminary study involved a semi-structured interview with one deaf participant, observations of short video clips, and document review of relevant blog entries by a deaf individual from Malaysia. Thematic analysis was completed, and six emerging themes found were access, communication/interaction, gaining perspectives, interpreters, optimistic, and social support. As this was a feasibility study, modifications were made throughout the study. Limitations of this study was documented and taken into consideration in designing further studies.